A new species of Chilicola from Bahia, Brazil (Hymenoptera, Colletidae), with a key to the species of the megalostigma group - Favizia Oliveira; Thiago Mahlmann; Michael Engel (ZooKeys, 2011)
The bee genus Chilicola Spinola (Xeromelissinae) is recorded from the State of Bahia, Brazil for the first time, based on a new species of the megalostigma group of the subgenus Hylaeosoma Ashmead. Chilicola (Hylaeosoma) kevani sp. n. is described and figured from males collected in Wesceslau Guimarães, Bahia. The species can be distinguished on the basis of coloration, size, integumental sculpturing, and structure of the hidden metasomal sterna and genitalia. A revised key to the species of the megalostigma group is provided.